MODERN REPRESENTATIONS OF THE ROLE POSTNATAL INDUCED NEOLYMPHANGIOGENESIS IN METASTATIC PROCESS - Sh. R. Kzyrgalin (Креативная хирургия и онкология, 2017)
The article presents an overview of the  literature on the  study  of the  mechanisms of formation of  intratumoral and  peritumoral lymphatic  vessels  in cancer  and  their  role in regional  and  distant metastasis.  Lymphangiogenesis complex  multifactorial process, the study of which helps to clarify the overall flow pattern of the tumor  process.